Level and determinants of postpartum adherence to antiretroviral therapy in the Eastern Cape, South Africa - Adeniyi, Oladele Vincent (PLoS One, 2020)
BACKGROUND: Adherence to antiretroviral therapy (ART), especially during the postpartum period, remains a major challenge in the efforts towards eliminating mother-to-child transmission of HIV. This study examined the levels and determinants of postpartum adherence to ART among mothers with HIV in the Eastern Cape, South Africa. METHODS: In this cross-sectional analytical study, we interviewed 495 postpartum women with HIV between January and May 2018. We measured postpartum adherence using six questions probing participants’ adherence behaviours since child birth. We categorised the adherence behaviours into complete adherence (mothers who reported no missed episode(s) of ART since child birth) and suboptimal adherence (mothers with any missed episode(s) of ART). Adjusted and unadjusted logistic regression models were used to examine the determinants of postpartum adherence to ART. RESULTS: Overall, 63.9% reported complete adherence during the postpartum period but the rates varied by socio-demographic and behavioural characteristics. The adjusted logistic regression analysis showed that younger mothers were 70% less likely to report complete adherence to ART compared to mothers aged 40 and above. Likewise, mothers who currently use alcohol were 53% less likely to report complete postpartum adherence to ART compared to those who did not use alcohol. However, mothers who knew their partner’s status were twice more likely to report complete postpartum adherence compared to those who did not. There was no statistically significant relationship between ART adherence and breastfeeding durations. CONCLUSION: Postpartum adherence to ART is suboptimal in the study setting, and younger mothers and those who use alcohol have a lower odds of complete adherence. Knowing a partner’s status improves adherence, but infant feeding practices did not influence postpartum adherence behaviours. It is critical to design and strengthen interventions which target young mothers and alcohol users. Also, HIV sero-status disclosure should be encouraged among mothers to facilitate partner support.